2013
DOI: 10.1073/pnas.1316463110
|View full text |Cite
|
Sign up to set email alerts
|

Correction for Tian et al., BRCA1 promotes the ubiquitination of PCNA and recruitment of translesion polymerases in response to replication blockade

Abstract: a 41. Pathania S, et al. (2011) BRCA1 is required for postreplication repair after UV-induced DNA damage. Mol Cell 44(2):235-251.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Calpain cleavage was discussed above. Citrullination of R3 and R5 residues within GSK3β is important for nuclear localization (Stadler et al, 2013). However, we observed that mTORC1 controls both GSK3α and GSK3β nuclear localization, and these two GSK3 paralogs differ at their N-terminus within the region of GSK3β that are expected to undergo citrullination.…”
Section: Specific Amino Acids Acutely Promote Gsk3 Nuclear Exportmentioning
confidence: 62%
See 2 more Smart Citations
“…Calpain cleavage was discussed above. Citrullination of R3 and R5 residues within GSK3β is important for nuclear localization (Stadler et al, 2013). However, we observed that mTORC1 controls both GSK3α and GSK3β nuclear localization, and these two GSK3 paralogs differ at their N-terminus within the region of GSK3β that are expected to undergo citrullination.…”
Section: Specific Amino Acids Acutely Promote Gsk3 Nuclear Exportmentioning
confidence: 62%
“…Other than phosphorylation, other modifications reported for GSK3β include citrullination (Stadler et al, 2013) and calpain cleavage (Goñi-Oliver et al, 2007). Calpain cleavage was discussed above.…”
Section: Specific Amino Acids Acutely Promote Gsk3 Nuclear Exportmentioning
confidence: 96%
See 1 more Smart Citation
“…3A,B), with the intensity of fluorescent lignin at the cortex-facing cell wall being consistently more prominent than the one at the pericycle-facing one. This pattern of ectopic lignification is precisely re-iterating the compensatory lignification observed in many other CS-defective mutants (31,33,39,40). It is known to depend on SCHENGEN (SGN) pathway activation and eventually leads to an alternative, though significantly delayed, formation of an apoplastic diffusion barrier in CS mutants.…”
Section: A Per3 9 39 72 64 Quintuple Mutant Is Devoid Of Casparian Stmentioning
confidence: 63%
“…1E). CASPs co-localize with other cell wall proteins at the CS, such as PEROXIDASE 64 (PER64) and ENHANCED SUBERIN 1 (ESB1), both involved in CS formation (2,33). Thus, laccases and peroxidases localize to the same cell wall domain in the endodermis.…”
Section: Protein Fusions Of Lac1 Lac3 Lac5 and Lac13 Accumulate At mentioning
confidence: 99%